Comparative Fault Detection Between DWT and STFT in Overcurrent Relays - Pathomthat Chiradeja; Santipont Ananwattanaporn; Praikanok Lertwanitrot; Atthapol Ngaopitakkul; A. Kunakorn (IEEE Access, 2024)
This study proposes a protection relay using a microcontroller to detect and classify faults in transmission lines based on the Wavelet transform. An experimental model was constructed from an actual 115 kV transmission system prototype. The current signal was observed based on the fault type, phase, and position. Clark’s transform and the discrete Wavelet transform (DWT) were applied to transform signals for analysis. The positive and zero sequences obtained from Clark’s transform were used for fault detection and fault classification, respectively. Moreover, the performances between the DWT and the short-time Fourier Transform (STFT) were compared in terms of accuracy and processing time. In addition, the double-detection technique was used to confirm the accuracy of fault detection. Results show that the proposed method is efficient for fault detection and classification. This finding allows the researcher to choose the appropriate analytical method. Moreover, it can also be used as the basis for overcurrent relay algorithm design in the effort to develop more advanced technologies.
Keywords: Power Systems Fault Detection; Islanding Detection in Power Systems; Power Transformer Diagnostics and Insulation